Implementasi pelatihan visual marketing melalui fotografi untuk memperkuat branding pemasaran - Ruby Chrissandy; Anny Valentina; David Amadeus Gerungan; Yosadara Paramita; Ruth Cecilia (Nur Science Institute, 2026)
Photography and visual communication skills play a critical role in supporting branding strategies in the digital era, particularly for university students who actively use social media. However, limited understanding of visual marketing techniques often weakens the effectiveness of brand communication. This community engagement activity aimed to improve participants' practical skills in photography-based visual marketing through an international workshop held at Kun Shan University on April 16, 2025. Ten undergraduate business students joined the session, which combined interactive presentations, case studies, group discussions, and smartphone photography practice. Engagement was strong, with 6 of 10 participants (60%) actively raising their hands and answering questions during the question and answer. Unlike conventional photography training, this activity emphasized visual branding for digital media, smartphone-based practice, a cross-cultural setting, and the integration of storytelling into brand identity. Participants showed improved ability to read visual elements and create engaging branded content, supporting the long-term development of students' visual-marketing competencies.